2018
DOI: 10.1016/j.buildenv.2017.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Parametric study of air curtain door aerodynamics performance based on experiments and numerical simulations

Abstract: Air curtains have been widely used to reduce infiltration through door openings and save heating/cooling energy in different types of buildings. Previous studies have found that there exist three aerodynamics conditions: optimum condition (OC), inflow break-through (IB), and outflow breakthrough (OB) conditions, which are important for categorizing air curtain performance subject to such key parameters including supply speed and angle, and presence of a person during an actual operation.However, few studies ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(19 citation statements)
references
References 21 publications
0
19
0
Order By: Relevance
“…However, there is no systematic approach to the contaminant aerodynamic sealing in the transition between the optimum condition and the 'inflow breakthrough condition'. The studies on the application of air curtains have been based on experiments [13,[26][27][28][29], on CFD models [23,29,30], and on semi-analytical models [12,31].…”
Section: (A) (B)mentioning
confidence: 99%
“…However, there is no systematic approach to the contaminant aerodynamic sealing in the transition between the optimum condition and the 'inflow breakthrough condition'. The studies on the application of air curtains have been based on experiments [13,[26][27][28][29], on CFD models [23,29,30], and on semi-analytical models [12,31].…”
Section: (A) (B)mentioning
confidence: 99%
“…3,15,3843 Qi et al. 33 presented a parametric study about air curtain performance. However, it was not developed to assess either the jet or the exhaust parameters that are to be fulfilled to keep the jet in the transition between the optimum condition and the ‘inflow breakthrough condition’.…”
Section: Introductionmentioning
confidence: 99%
“…The study of the use of air curtains to avoid contaminant spreading has been reported, for tobacco smoke control, 17,18 for operating rooms, 7,[19][20][21][22][23][24] in offices, 25 for protection of art works in museums and of cultural heritage, 26,27 in personalized air curtains, 28 in open refrigerated display cabinets [29][30][31] and in public transportation. 32 The studies on the performance of air curtains have been based on CFD models, 25,27,28,31,[33][34][35][36] on semi-analytical models, 16,37 and on experiments. 3,15,[38][39][40][41][42][43] Qi et al 33 presented a parametric study about air curtain performance.…”
Section: Introductionmentioning
confidence: 99%
“…For validating the CFD model of air curtain, velocity profile of complete system considered during analysis for different pressure difference that is 0.2, 3.6, 6.4, 7.3 and 8.7 Pa were taken and then it is compared with the velocity profile obtained during the experimental analysis performed by Goubran et.al [1]. Through numerical analysis, the value of volume flow rate of air at outer outlet of door during intrinsic and extrinsic condition is calculated.…”
Section: Validation Of Cfd Modelmentioning
confidence: 99%